স্বাধীন বাংলা বেতার কেন্দ্রের ইতিহাস - প্রধান, জাহিদ হোসেন
History of Svādhīna Bāṃlā Betāra Kendra, first independent radio station in Bangladesh started at the time of the independence struggle in 1971; contributed articles.